HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN KOMITMEN GURU DALAM MELAKSANAKAN TUGAS DI SMK N 2 PARIAMAN - FITRI NELDA (Universitas Negeri Padang, 2016)
This study aimed to describe the teachers 'commitment to implementing the tasks, school leadership and school leadership with teachers' commitment to carry out tasks in vocational high schools 2 pariaman country. The population is 102 people and the sample 87 using Table Kriecje with stratified random sampling technique. Instruments used a Likert scale. Statistical data analysis techniques using correlation techniques using SPSS 16.0 for Windows. The result showed that: (1) Leadership principals to be in either category 88.31%. (2) The commitment is in the category of High 89.29%, (3) there is a significant relationship between school leadership and teachers' commitment to carry out the task with correlation coefficient=0,288. keywords: leadership, commitment